Unity 2018 Shaders and Effects Cookbook : Transform Your Game into a Visually Stunning Masterpiece with over 70 Recipes, 3rd Edition. - Zucconi, Alan (Packt Publishing Ltd, 2018)
Shaders have always been seen as notoriously difficult to understand and implement in games. Complex math have always stood in the way of attaining realism in games. This book shows you everything you need to know about vectors, constructing lighting with them, and using textures to create complex effects without the heavy math.